Evaluation of the efficacy of loricrin as a diagnostic marker in patients with oral submucous fibrosis - Niva Mahapatra; Kailash C Dash; Lipsa Bhuyan; Abikshyeet Panda; Shyam S Behura; Pallavi Mishra (Wolters Kluwer Medknow Publications, 2020)
Introduction: Loricrin is usually observed in abundance in keratinizing epithelium in response to mechanical stress, which may be associated with development and malignant transformations in conditions such as oral submucous fibrosis (OSMF). Therefore, understanding of various molecular mechanisms associated with difference in gene expressions between OSMF and that of normal oral tissue is important. Aim: The aim of this study was to evaluate of the efficacy of loricrin as a diagnostic marker in patients with OSMF. Materials and Methods: Fifty formalin-fixed paraffin-embedded tissue blocks were obtained from the archives of the department. The study sample was grouped into two groups of normal mucosa (group I; n = 20) and OSMF (group II; n = 30) specimens. The study tissues were immunohistochemically stained with loricrin antibody and were further graded on basis of staining intensity. Results: Loricrin immunostaining was observed significantly more in OSMF cases and even in stratum granulosum in comparison to normal mucosa. Conclusion: Loricrin can act as an early indicator and a prognostic marker for detection of deleterious changes within epithelium in OSMF.